Investor-driven corporate finance: Evidence from insurance markets - Christian Kubitza (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2021)
This paper documents that the bond investments of insurance companies transmit shocks from insurance markets to the real economy. Liquidity windfalls from household insurance purchases increase insurers' demand for corporate bonds. Exploiting the fact that insurers persistently invest in a small subset of firms for identification, I show that these increases in bond demand raise bond prices and lower firms' funding costs. In response, firms issue more bonds, especially when their bond underwriters are well connected with investors. Firms use the proceeds to raise investment rather than equity payouts. The results emphasize the significant impact of investor demand on firms' financing and investment activities.
Keywords: 330; Corporate Finance; Corporate Bonds; Insurance; Real Effects